2023
DOI: 10.3389/fceld.2023.1169966
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted promotion of apoptosis by acetylcholinesterase

Abstract: Elevated expression of acetylcholinesterase (AChE) is a common characteristic of apoptotic cells in both invertebrate and vertebrate species. While increased levels of acetylcholinesterase sensitize cells to apoptogenic stimuli, its absence or pharmacological inactivation interferes with apoptotic cell death. acetylcholinesterase may exert its pro-apoptotic function directly as an integral component of the apoptotic molecular machinery or indirectly by limiting the availability of receptor ligands and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
1
1
0
Order By: Relevance
“…AChE is considered to be a key regulatory enzyme in the cholinergic nervous system [70]. Increased AChE activity makes the cell more susceptible to apoptosis and serves as an intrinsic regulator of inflammation [71,72]. In the present investigation, LPS administration resulted in the enhancement of AChE activity, which correlates with several previous studies [73,74].…”
Section: Prophylactic Effect Of Sfn Against Ache Overactivation Induc...supporting
confidence: 90%
“…AChE is considered to be a key regulatory enzyme in the cholinergic nervous system [70]. Increased AChE activity makes the cell more susceptible to apoptosis and serves as an intrinsic regulator of inflammation [71,72]. In the present investigation, LPS administration resulted in the enhancement of AChE activity, which correlates with several previous studies [73,74].…”
Section: Prophylactic Effect Of Sfn Against Ache Overactivation Induc...supporting
confidence: 90%
“…Another possible explanation for the AChE activity increase appointed in the literature is cell apoptosis, a form of programmed cell death with important roles in development, tissue homeostasis, and various diseases [83]. Studies have been investigating the relation between AChE and apoptosis and have demonstrated that AChE also plays an important role as a regulator of apoptosis (caused by oxidative stress) and that apoptogenic stimuli may increase AChE levels in organisms, including invertebrates [84]. Moreover, at higher concentrations, higher NPs aggregation may have occurred, which could have prevented the action of PMMA NPs at higher concentrations, since larger particles cannot penetrate cell membranes; therefore, organisms exposed to lower concentrations were more affected.…”
Section: Discussionmentioning
confidence: 99%